Research gaps in STEM-integrated project-based learning for critical thinking in physical education: A bibliometric analysis - Rahayu Prasetiyo; Arsika Yunarta; M. Zaim Zen (Sriwijaya Journal of Sport, 2026)
Research Problems: Project-Based Learning integrated with Science, Technology, Engineering, and Mathematics (STEM-PjBL) has been widely recognized as an effective instructional approach for fostering higher-order thinking skills, particularly critical thinking. However, its application within Physical Education (PE) remains underexplored, and the current research landscape has not been comprehensively mapped. Research Objectives: This study aimed to identify research trends, collaboration patterns, conceptual structures, and research gaps related to STEM-integrated Project-Based Learning (STEM-PjBL) for enhancing critical thinking skills, with particular emphasis on its application in Physical Education, using a bibliometric approach. Methods: A bibliometric analysis was conducted using the Dimensions database. Publications were retrieved using the search query ("STEM") AND ("Project-Based Learning" OR "PjBL") AND ("Critical Thinking") AND ("Physical Education"). The search was performed on April 21, 2026, covering publications from 2020 to 2026, and yielded 1,024 documents that met the inclusion criteria. Data were analyzed using VOSviewer through performance analysis and science mapping techniques, including publication trend analysis, author and country collaboration networks, institutional productivity, keyword co-occurrence, density visualization, and overlay visualization. Results: The findings revealed a substantial increase in STEM-PjBL publications during the study period, with research predominantly concentrated in science, mathematics, engineering, and technology education. Collaboration network analysis indicated a semi-fragmented research structure, with the United States and Indonesia emerging as the most influential contributors. Keyword co-occurrence analysis identified four major research clusters: learning evaluation, teacher professional development, technology integration, and STEM academic domains. Despite this growth, Physical Education remained a peripheral research topic and was not yet strongly integrated into the global conceptual structure of STEM-PjBL research. Overlay visualization further indicated that studies linking STEM-PjBL, critical thinking, and Physical Education are still limited, highlighting an important research gap. Conclusion: This bibliometric study demonstrates that the integration of STEM-PjBL into Physical Education remains underdeveloped despite the rapid growth of STEM-PjBL research in other educational disciplines. The findings provide evidence of significant opportunities for future research to develop and evaluate contextual STEM-PjBL models that promote critical thinking through project-based physical activities and technology-supported learning. This study contributes to the understanding of current research trends and offers a strategic direction for advancing interdisciplinary innovation in Physical Education.